1999
DOI: 10.1002/(sici)1097-0142(19991015)86:8<1437::aid-cncr8>3.3.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of transfusion‐transmitted virus among patients with non‐B, non‐C hepatocellular carcinoma

Abstract: This study showed that TTV DNA is frequently detected in the serum of patients with non-B, non-C hepatocellular carcinoma. This result suggests a potential pathogenetic association between hepatocellular carcinoma and TTV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Furthermore, retrospective analyses of patients treated with alpha interferon with or without ribavirin for underlying HCV infection have shown that therapy may result in a generally transient disappearance of detectable TTV from blood, especially if baseline TTV viremia is low, but that this is not accompanied by modulation of ALT levels unless HCV is also cleared (4,8,16,48). In addition, attempts to link TTV to hepatocellular carcinoma in patients positive or negative for HBV and HCV have given inconsistent results (107,132,156,184). Undoubtedly, the above observations rule out the notion that clinically evident liver disease is a frequent consequence of TTV infection.…”
Section: Clinical Significancementioning
confidence: 99%
“…Furthermore, retrospective analyses of patients treated with alpha interferon with or without ribavirin for underlying HCV infection have shown that therapy may result in a generally transient disappearance of detectable TTV from blood, especially if baseline TTV viremia is low, but that this is not accompanied by modulation of ALT levels unless HCV is also cleared (4,8,16,48). In addition, attempts to link TTV to hepatocellular carcinoma in patients positive or negative for HBV and HCV have given inconsistent results (107,132,156,184). Undoubtedly, the above observations rule out the notion that clinically evident liver disease is a frequent consequence of TTV infection.…”
Section: Clinical Significancementioning
confidence: 99%
“…Numerous investigations also revealed that the presence of TTV‐DNA was not associated with liver injury, 17,22 acute fulminant and non‐fulminant hepatitis, 21 or hepatocellular carcinoma 24 . In contrast, some other reports showed that TTV was suggested to be associated with elevated ALT levels, 1,2 , 25,26 and may play a role in the development of chronic liver diseases of unknown etiology 1,27 or even hepatocellular carcinoma 28 . One of the possible explanations as to why the difference existed regarding the pathogenesis between studies may be that there was a difference in pathogenesis that depended on the TTV genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic infection with HGV may play a role in the development of HCC in non‐Asians in Los Angeles 6 . A high prevalence of TTV infection has been detected among patients with non‐B, non‐C HCC, suggesting a potential association between TTV infection and HCC 7 . The risk of dietary iron overload was 4.1 for HCC in black African people 8 .…”
Section: Aetiology Prevention and Hepatocarcinogenesismentioning
confidence: 99%